New species of haematozoa from the avian families Campephagidae and Apodidae - Barraclough R.K.; Robert V.; Peirce M.A. (Parasite, 2008)
Leucocytozoon coracinae sp. nov. is described from the avian family Campephagidae and Hepatozoon apodis sp. nov. from the Apodidae. The distribution of these parasites within their respective families is discussed.